2016
DOI: 10.17305/bjbms.2016.841
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of laparoscopic transversus abdominis plane block for elective laparoscopic cholecystectomy in elderly patients

Abstract: Transversus abdominis plane (TAP) block technique seems to off er one of the most effi cient methods for a local pain control. Our aim is to demonstrate the eff ectiveness and safety of TAP block for post-operative pain control under laparoscopic vision in elderly patients during laparoscopic cholecystectomy. Th e patients aged more than 65 years old, who had cholecystectomy due to symptomatic cholelithiasis, were retrospectively evaluated. Th e patients that were operated under general anesthesia + laparoscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 36 publications
(39 reference statements)
3
14
1
Order By: Relevance
“…When Tihan et al (17) reaserched the effectiveness of laparascopic TAP block on VAS scores on patients who are olther than 65 and heve undergone laparoscopic cholecystectomy, have similar results as our study. VAS scores were lower in the TAP block administered group than the control group and this was statistically significant (17).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…When Tihan et al (17) reaserched the effectiveness of laparascopic TAP block on VAS scores on patients who are olther than 65 and heve undergone laparoscopic cholecystectomy, have similar results as our study. VAS scores were lower in the TAP block administered group than the control group and this was statistically significant (17).…”
Section: Discussionsupporting
confidence: 86%
“…When Tihan et al (17) reaserched the effectiveness of laparascopic TAP block on VAS scores on patients who are olther than 65 and heve undergone laparoscopic cholecystectomy, have similar results as our study. VAS scores were lower in the TAP block administered group than the control group and this was statistically significant (17). Moreover, in a study, in which 40 elective caesarean patients divided in two groups as USG guided TAP block performed and without TAP block, it was also shown that post operative VAS scores were statistically significantly lower in TAP block group than the controle group (18).…”
Section: Discussionsupporting
confidence: 86%
“…Afterward, Chetwood et al [23] used a similar method following laparoscopic nephrectomy which was safe and time saving. In addition, laparoscopic-guided TAP block has reduced postoperative pain scores after laparoscopic cholecystectomy [24,25] and laparoscopic ventral hernia repair [26].…”
Section: Discussionmentioning
confidence: 99%
“…For the sample size calculation, a minimum difference of 2 between two VAS measurements was considered, assuming a standard deviation of 2, per group. The previous studies found a 1.3 standard deviation for TAP [23] and an interquartile range of 2 to 3 [4]. To randomize patients into the groups, a 1:1 allocation ratio was used for a power of 80%, and hypotheses tested at alpha level (p-value) of 0.017, using the Bonferroni correction to adjust the 0.05 level of confidence three times, since three comparisons for the three groups were done.…”
Section: Sample Size Calculationmentioning
confidence: 99%
“…The laparoscopic cholecystectomy is a minimally invasive, widespread surgical procedure, associated with postoperative pain of moderate intensity in the early postoperative period. The pain reaches its peak within the first few hours after surgery and diminishes during the next two to three days [1][2][3][4]. There are several approaches to postoperative pain management after laparoscopic cholecystectomy, such as intravenous patient-controlled analgesia with opioids (IV-PCA), neuraxial blocks, intraperitoneal local anesthesia, and wound infiltration.…”
Section: Introductionmentioning
confidence: 99%